2020
DOI: 10.3390/plants9040460
|View full text |Cite
|
Sign up to set email alerts
|

Silicon in Horticultural Crops: Cross-talk, Signaling, and Tolerance Mechanism under Salinity Stress

Abstract: Agricultural land is extensively affected by salinity stress either due to natural phenomena or by agricultural practices. Saline stress possesses two major threats to crop growth: osmotic stress and oxidative stress. The response of these changes is often accompanied by variety of symptoms, such as the decrease in leaf area and internode length and increase in leaf thickness and succulence, abscission of leaves, and necrosis of root and shoot. Salinity also delays the potential physiological activities, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 176 publications
(217 reference statements)
1
35
0
1
Order By: Relevance
“…Environmental stress factors such as salinity [6][7][8][9], drought [10][11][12][13][14][15][16], chilling, and heat stress [17,18] negatively affect crop productivity in many plants. Salinity is an abiotic harmful stress factor, affecting structure, physiochemical characters, and the ecology of the soil, as well as the growth and plant yield [19][20][21]. The total area of saline and sodic soils was determined (831 million ha) worldwide according to the FAO report [22].…”
Section: Introductionmentioning
confidence: 99%
“…Environmental stress factors such as salinity [6][7][8][9], drought [10][11][12][13][14][15][16], chilling, and heat stress [17,18] negatively affect crop productivity in many plants. Salinity is an abiotic harmful stress factor, affecting structure, physiochemical characters, and the ecology of the soil, as well as the growth and plant yield [19][20][21]. The total area of saline and sodic soils was determined (831 million ha) worldwide according to the FAO report [22].…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al found that, compared to the control group, an analogous Si dosage (4 g kg −1 soil) was sufficient to increase the germination rate, plant height, root weight and fresh weight of pak choi [ 12 ]. With regard to the declined growth indexes and available Si content in pak choi, as Si-OPC dosage was increased from 5 to 60 g kg −1 soil, in addition to the soil pH rise, another possible reason accounting for this phenomenon is the increase in soil salinity, which might give rise to (1) the inhibition of photosynthesis, owing to the triggered close of stomata and disturbance of the CO 2 -to-O 2 ratio in leaves [ 51 ], (2) and the plasmolysis of plant cell because of the exorbitant osmotic pressure, and therefore impair the cellular metabolism [ 6 ]. In particular, in the case of the optimum Si-OPC application (5 g kg −1 soil), the resultant exchangeable calcium content in the soil was 9.47 cmol/kg soil, with this value in the range of moderate calcium level (5–10 cmol/kg) in soil [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ti is well known to be an element that when found in soils and waters used for plant growth, it enhances not only the plants' photosynthesis, but also their chlorophyll content, which promotes nutrient uptake, better stress tolerance, and improves crop yield and quality, making this a beneficial element (Lyu et al 2017). On the other hand, the beneficial effects of silicon to plants are widely demonstrated (Murad et al 2020) and its oxidised form (SiO 2 NPs) promoted plant protection against biotic and abiotic stress (Luyckx et al 2017). Our work contains the first results addressing TiSiO 4 NPs photosynthetic bioactivity in plants, and we demonstrate that, after short-term exposure, moderate doses of TiSiO 4 NPs might stimulate lettuce growth, and may positively influence, in yet to unveil mechanisms, photosynthetic parameters, such as the increase of photosynthetic pigments at lower doses (50 mg/L) and gas exchange and PSII efficiency at higher doses (100 mg/L).…”
Section: Discussionmentioning
confidence: 99%